A multidisciplinary approach and implementation of a specialized hemorrhage control team improves outcomes for placenta accreta spectrum. Issue 5 (May 2021) - Nieto-Calvache, Albaro José; Vergara-Galliadi, Lina María; Rodríguez, Fernando; Ordoñez, Carlos A.; García, Alberto Federico; López, María Camila; Manzano, Ramiro; Velásquez, Jorge; Carbonell, Juan Pablo; Bryon, Adriana Messa; Echavarría, Maria Paula; Escobar, Maria Fernanda; et al.
Abstract : INTRODUCTION: The main complication of placenta accreta spectrum (PAS) is massive bleeding. Endoarterial occlusion techniques have been incorporated into the management of this pathology. Our aim was to examine the endovascular practice patterns among PAS patients treated during a 9-year period in a low-middle income country in which an interdisciplinary group's technical skills were improved with the creation of a PAS team. METHODOLOGY: A retrospective cohort study including all PAS patients treated from December 2011 to November 2020 was performed. We compared the clinical results obtained according to the type of endovascular device used (group 1, internal iliac artery occlusion balloons; group 2, resuscitative endovascular balloons of the aorta; group 3, no arterial balloons due to low risk of bleeding) and according to the year in which they were attended (reflects the PAS team level of experience). A fourth group of comparisons included the woman diagnosed during a cesarean delivery and treated in a nonprotocolized way. RESULTS: A total of 113 patients were included. The amount of blood loss decreased annually, with a median of 2, 500 mL in 2014 (when endovascular occlusion balloons were used in all patients) and 1, 394 mL in 2020 (when only 38.5% of the patients required arterial balloons). Group 3 patients (n = 16) had the lowest bleeding volume (1, 245 mL) and operative time (173 minutes) of the entire population studied. Group 2 patients (n = 46) had a bleeding volume (mean, 1, 700 mL) and transfusions frequency (34.8%) slightly lower than group 1 patients (n = 30) (mean of 2, 000 mL and 50%, respectively). They also had lower hysterectomy frequency (63% vs. 76.7% in group 1) and surgical time (205 minutes vs. 275 in group 1) despite a similar frequency of confirmed PAS and S2 compromise. CONCLUSION: Endovascular techniques used for bleeding control in PAS patients are less necessary as interdisciplinary groups improve their surgical and teamwork skills. LEVEL OF EVIDENCE: Therapeutic care management, level III. Abstract : Supplemental digital content is available in the text.